2002
DOI: 10.1088/0960-1317/12/5/322
|View full text |Cite
|
Sign up to set email alerts
|

Design and fabrication of artificial lateral line flow sensors

Abstract: Underwater flow sensing is important for many robotics and military applications, including underwater robots and vessels. We report the development of micromachined, distributed flow sensors based on a biological inspiration, the fish lateral line sensors. Design and fabrication processes for realizing individual lateral line sensor nodes are discussed in this paper, along with preliminary characterization results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
153
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(157 citation statements)
references
References 26 publications
3
153
0
1
Order By: Relevance
“…Modelling the pressure sensing after natural or artificial devices (Fan et al 2002;Coombs & Braun 2003;Yang et al 2006), we assume a finite noise-tosignal ratio g in that measurement. This noise level primarily accounts for two sources of ubiquitous noise: the noise induced by the limited capabilities of the mechanotransducers forming the sensing device as well as the signal postprocessing; and the background noise of the fluid flow in which the sensor is placed.…”
Section: Problem Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modelling the pressure sensing after natural or artificial devices (Fan et al 2002;Coombs & Braun 2003;Yang et al 2006), we assume a finite noise-tosignal ratio g in that measurement. This noise level primarily accounts for two sources of ubiquitous noise: the noise induced by the limited capabilities of the mechanotransducers forming the sensing device as well as the signal postprocessing; and the background noise of the fluid flow in which the sensor is placed.…”
Section: Problem Definitionmentioning
confidence: 99%
“…Manoeuvrability requires acute sensing capabilities which can more easily be obtained through multi-modal sensory systems and devices. From the robotic standpoint, Fan et al (2002) reported the first design and fabrication of an artificial lateral line flow sensor. Later, Yang et al (2006) reported the first experimentations where such an artificial LLS is used to detect both a dipole and a wake, hence allowing it to mimic the pressure-sensing capabilities of those encountered in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Fan et al [19] have made an ALLS by fabricating hair flow sensors, using microelectromechanical systems (MEMS) technology. Franosch et al [30] have developed an ALLS prototype with a single hot-thermistor anemometric sensor positioned onto an underwater robotic system.…”
Section: Lateral-line Systemmentioning
confidence: 99%
“…This design is favoured since the protruding structures escape unwanted boundary layer effects. Several techniques used for strain sensing include lamella mechanical micro-sensors (MEMs) (Fan et al 2002, McConney et al 2009, Yang et al 2007, 2010, ionic polymer-metal composites (IPMC) (Abdulsadda and Tan 2012, Chen et al 2013 and soft polymer membranes without (Asadnia et al 2013) and with cantilever structures (Kottapalli et al 2014. A technical review of recent contributions to the field of artificial neuromast and artificial lateral lines (ALL) shows an increasing interest in this field (Liu et al 2016).…”
Section: Introductionmentioning
confidence: 99%